Hands-on artificial intelligence on Amazon Web Services : decrease the time to market for AI and ML applications with the power of AWS - Tripuraneni, Subhashini; Song, Charles (Packt Publishing, Limited, 2019)
AI in AWS covers primarily two broad topics - a) how to leverage readily available AI/ML APIs and b) how to build, train and deploy ML models from scratch, to solve diverse business problems, such as demand forecasting, image classification, topic modeling, speech and text recognition.